The Effect of Electrophoretic Deposition Current to Tinplate Coating with Chitosan - Gapsari, Femiana; Setyarini, Putu H.; Fajrin, Erfinda F. (International Journal of Integrated Engineering, 2019)
This study was a preliminary study in applying chitosan as coating for tinplate. Tinplate is used as material for packaging because it is cheap, attractive, shiny, and easy to shape. Chitosan coating on tinplate with electrophoretic deposition (EPD) method and variation of EPD current was performed in this study. the variation of the current was 2, 4, 6,and 8 A. Coating thickness was measured using NOVOTEST TP-1M. The surface roughness was tested using Mitutoyo Surface Roughness Tester SJ-210. Corrosion test applied the polarization method of Potentiodynamic Autolab PGSTAT 128N with Control software NOVA 1.11. The corrosion test of the specimen was run in 3.5% NaCl solution. The specimens without treatment had higher corrosion rate compared to the specimen with EPD current of 8A which was 0.00061927 mpy. At the current variation of 8A, the coating thickness was 78.9 Â± 1.58 %.The higher the current used in the EPD the lower the corrosion rate was. It was indicated by coating which protected tinplate and produced homogeneous coating. This was in line with the result of surface roughness which decreased with the increase of EPD current. The lowest surface roughness was at variation of 8A which was 0.152 Âµm.